Emerging Frontline Leaders' Voices in Response to COVID-19 Crisis. Issue 2 (March 2022) - Taha, Asma A.; Zhang, Zhenzhen; Driessnack, Martha; Huntzicker, James J.; Eisen, Aaron M.; Bernstein, Juliana; Chen, Aiyin; Chandra, Ravi A.; Drake, Karen; Fung, Alice; Ladkany, Rand; LaVigne, Brenda; et al.
Abstract : Background: The COVID-19 pandemic has significantly affected healthcare institutions, introducing new challenges for nurse leaders and their colleagues. However, little is known about how the pandemic has specifically affected the lives of these leaders and what methods and strategies they are using to overcome pandemic-related challenges. Objectives: The aim of this study was to examine the effect of the 2019 pandemic on emerging healthcare leaders and highlight methods and strategies they used to overcome pandemic-related challenges. Methods: The participants in this study represent a diverse group of interprofessional healthcare faculty enrolled in a transformational leadership course (Paths to Leadership) when the pandemic first appeared. Three months into the pandemic, the leadership cohort was invited to participate in this qualitative study, exploring four questions: Q1: How have you transformed your working styles in response to the pandemic? Q2: How have you adjusted your personal life in response to the pandemic? Q3: How have you used leadership skills learned from Paths to Leadership during the pandemic? Q4: What lessons have you learned from the pandemic? Participant narratives were analyzed by a team of nurse researchers using conventional qualitative content analysis. Results: Themes for Q1 (working styles) included shifted from face-to-face to telework, faced novel disease and decisions, worked more from home, and challenged to maintain contact with professional peers and team . Themes for Q2 (personal life) included accommodate adults working and children learning from home, looked for and found the positive, and continue to struggle . Themes for Q3 (leadership skills) included reflective practice, listening, holding, and reframing . Finally, themes for Q4 (pandemic lessons) included leadership, human connection, be prepared, taking care of ourselves, and connecting with nature . Discussion: The 2019 pandemic brought hardships and opportunities to faculty members enrolled in an interprofessional transformational leadership course. In conjunction with this course, the pandemic provided a unique opportunity for participants to apply newly acquired relationship building, positive organizational psychology, and reframing skills during a time of crisis. Nursing leaders, whose educational offerings may be immediately "put to the test, " may find our lessons learned helpful as they develop strategies to cope with unanticipated future challenges. Abstract : Supplemental digital content is available in the text.